Value Stream Mapping in MEP Work on the Pondok Tjandra Project – Surabaya - Felicia Tria Nuciferani; Siti Choiriyah; Feri Harianto; Mila Kusuma Wardani; Siti Nuraini (Jurnal Teknologi dan Manajemen, 2024)
During construction, waste often occurs, not only material waste, but waste can also occur in activities that do not provide added value. Waste can result in cost losses and time delays in implementing a construction project. Value Stream Mapping (VSM) is a method that can be used to minimize waste by classifying activities into value added, non value added but necessary, and non value added. Mechanical engineering work was identified in the Pondok Tjandra Sidoarjo project, namely value added as many as 69 activities (67.65%), and non value added s as many as 17 activities (16.67%), while non value added but necessary as many as 16 activities (15.69%). The largest percentage of Non Value Added (NVA) is in AC work, namely 23.53%. The activities that are classified as waste are the preparation of labor tools/equipment, work delays due to waiting for the dismantling of formwork left over from structural work, breaking down light brick walls for refrigerant pipe lines conduilt pipes, and activities for the process of breaking down light brick walls again.